Case Report: Leaflet Thrombosis After Transcatheter Aortic Valve Replacement With Worsening Heart Failure—A Successful Resolution Using Non-vitamin K Antagonist Oral Anti-coagulant - Liang, Kae-Woei; Yu, Chu-Leng; Lin, Wei-Wen; Lee, Wen-Lieng (Frontiers in Cardiovascular Medicine, 2021)
Background: Transcatheter aortic valve replacement (TAVR) is indicated for treating symptomatic severe aortic valve stenosis (AS) with intermediate-to-high surgical risks. Few reports are available on managing leaflet thrombosis after TAVR with worsening heart failure. Case Summary: A 77-year-old man with severe AS and coronary artery disease (CAD) received a successful TAVR with Edwards Sapien 3 valve. A year later, the patient developed a worsening heart failure with pulmonary edema, new-onset atrial fibrillation (Af), an increase in mean trans-aortic valve pressure gradient to 48 mmHg, worsening mitral regurgitation (MR), and pulmonary hypertension (PH). The response of the patient to intravenous diuretics and inotropic treatments was poor. Multi-slice CT (MDCT) revealed hypo-attenuated thrombus and thickened transcatheter heart valve leaflets. A non-vitamin K antagonist oral anti-coagulant (NOAC) was added to treat the new-onset Af and leaflet thrombosis on top of the con-current single antiplatelet for CAD. A series of follow-up echocardiograms showed a progressive decrease in trans-aortic valve pressure gradient to 17 mmHg and reductions in MR and PH. Three months after the NOAC treatment, MDCT revealed the resolution of hypo-attenuated thrombus and thickened leaflets. Symptoms of heart failure were also improved gradually. Discussion: Worsening heart failure or an increase in trans-aortic valve pressure gradient after TAVR warranted further MDCT studies. Leaflet thrombosis can be resolved after using NOAC as in our present case.